Pondok Pesantren Al-Fatah Temboro sebagai Induk Madrasah Asia Selatan Berbasis Jama’ah Tabligh di Indonesia - Kholili Badriza (Sekolah Tinggi Agama Islam Program Studi Sejarah dan Kebudayaan Islam, 2022)
Pesantren al-Fatah located in Temboro, Karas, Magetan, East Java, prefers a South Asian affiliation, especially India and Pakistan, as a scientific “qibla”. Apart from adopting the South Asian Islamic scientific tradition, the pesantren also embraced South Asian Islamic characteristics. On that account, this research investigated the following topics: (1) How did the adoption process of South Asian Madrasas instruction model at al-Fatah occur? (2) To what extent is South Asian Madrasas’ educational model implemented at al-Fatah? (3) To what extent does the South Asian Islamic characteristic appear in the institution? Historical inquiries are employed as a method along with cultural approaches helping the analysis. These are several findings obtained from the study. First, the adoption of South Asian Madrasas’ instruction model at al-Fatah was strongly motivated by the institution’s “officially” adopted ideology, The Tablîghî Jamaʽât Movement. Second, the shifted directions of the instructional model that occur at al-Fatah are quite adaptive in maintaining certain elements of the original Indonesian pesantren. The pesantren also has a strong orientation towards becoming The Indian’s famous Darul Uloom Deoband version of Indonesia. Third, Islam in al-Fatah is characterized by 3 main maslak (school of thoughts): Deobandi, Tablighi Jamaat, and Nahdlatul Ulama.